(untitled) (Research, Society and Development, 2023)
Sexual activity represents one of the most important pillars of health and quality of life for human beings. It is a subject that is still very little studied, especially when it comes to the female sex. During graduation, with the numerous challenges that students face in their routines, they can significantly disrupt their sexual health. The study, therefore, aimed to evaluate the sexual response cycle, encompassing desire, excitement, orgasm and resolution of FAG medical students, evaluating female sexual performance and satisfaction of these students during the medical course. Therefore, a previously validated research instrument was applied, in the form of a questionnaire, called Sexual Quotient - Female Version (QS-F), developed by ProSex at USP. The work had 257 participants, of which 104 were students from the basic cycle, 119 from the clinical cycle and 34 from the internship. With regard to sexual function, 45.1% of the students had a regular to good sexual performance, scoring between 62-80 points in the questionnaire. It was concluded that the standard of sexual performance of medical students was adequate. However, about 17.2% of the participants showed an inadequate performance pattern.